2020
DOI: 10.1016/j.resp.2020.103494
|View full text |Cite
|
Sign up to set email alerts
|

High altitude reduces infection rate of COVID-19 but not case-fatality rate

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
86
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 21 publications
9
86
5
3
Order By: Relevance
“…Previous studies indicate the association between altitude and COVID-19 infection (Arias-Reyes et al, 2020;Segovia-Juarez et al, 2020). Our results give additional information about effect of altitude and population density on COVID-19 infection in a follow-up period of weeks from the first reported case in each region, which is important because of the unequal propagation of COVID-19 cases to altitude regions.…”
mentioning
confidence: 50%
“…Previous studies indicate the association between altitude and COVID-19 infection (Arias-Reyes et al, 2020;Segovia-Juarez et al, 2020). Our results give additional information about effect of altitude and population density on COVID-19 infection in a follow-up period of weeks from the first reported case in each region, which is important because of the unequal propagation of COVID-19 cases to altitude regions.…”
mentioning
confidence: 50%
“…8 However, other studies reported that elevated altitude does not induce a decrease in the COVID-19 case fatality rate. 9,10 Considering this background, we decided to examine the scenario of positive cases, deaths, and the case fatality rate of COVID-19 in Colombia in an altitude range from 1 to 3,180 m above sea level. Data from 70 municipalities affected by the pandemic were used, including the 32 departmental capital cities of the country.…”
mentioning
confidence: 99%
“…We have read with interest the short communication published by Segovia-Juarez et al, 2020 in Respiratory Physiology & Neurobiology establishing that high altitude reduces the infection rate of COVID-19 but not the case fatality rate in the Peruvian setting. We support this hypothesis, however there could be an important number of under registered deaths on account of a low rate of diagnostic tests performed per inhabitant and mostly in symptomatic patients ( Pasquariello and Stranges, 2020 ).…”
mentioning
confidence: 99%
“…Moreover, we used district altitudes in our analysis because Peruvian geography is greatly variable, and within a single province there may be a great difference between the altitude of different cities and towns. Hence, we believe a district altitude-based approach reduces the bias that may arise by altitude variability, which characterizes the province altitude-based approach used by Segovia-Juarez et al, 2020
Fig. 1 Correlation between excess mortality rate and altitude.
…”
mentioning
confidence: 99%